(untitled) (TAMADDUN NURI JURNALI, 2025)
There are various opinions regarding the time when the work was written or compiled. The author himself does not provide a clear indication about this. Nevertheless, through a careful reading of the "Baburnama", as well as studying its translations and research in foreign languages, analyzing the sources mentioned, examples of events by year, and its writing style, and closely examining the duality present in the text, one is led to believe that the work was written between 1525 and 1530.